Optimization of dry-season sap flow measurements in an oak semi-arid open woodland in Spain - Reyes-Acosta, J Leonardo; Lubczynski, Maciek W (Ecohydrology, 2012)
In sap flow studies, there is no method complying with high efficiency and versatility of sap flow measurements. To improve that, we propose combining two methods: (1) thermal dissipation probe (TDP) known to be efficient and cost effective and (2) heat field deformation (HFD) known to be versatile. For that purpose, we used a step-wise TDP sap flux density (Jp) optimization method consisting of (1) natural temperature gradient (NTG) correction applying the cyclic heat dissipation (CHD) method, (2) night flow ΔTmax correction using HFD data as reference and (3) radial-azimuthal correction using HFD as reference. We applied this optimization method on Quercus ilex (Q.i.) and Quercus pyrenaica (Q.p.) trees in a Spanish semi-arid open woodland during dry season. The NTG correction resulted in substantial reduction of Jp as compared with standard TDP. The subsequent ΔTmax night flow correction resulted in the increase of NTG-corrected Jp and good agreement with the outermost 2 cm of HFD measurements for both species. The final radial-azimuthal adjustment of TDP Jp resulted not only, in a good agreement with HFD Jp, but also provided novel ecohydrological insights such as: (1) evidence of continuous night flow in all Q.p. trees and some Q.i. trees, (2) exponential reduction of Jp with sapwood depth for both species, (3) significantly larger Jp in the outermost 1 cm of sapwood for Q.p. than for Q.i. and (4) high azimuthal Jp variability for both species. The presented study offers efficient and versatile method of tree sap flow measurements that contributed to a better understanding of water-related dynamics of Q.i. and Q.p. under water-stress conditions. Copyright © 2012 John Wiley & Sons, Ltd.
Keywords: HFD; natural temperature gradient; Quercus ilex; Quercus pyrenaica; radial and azimuthal sap flow variability; sap flow; semi-arid open forest; TDP